Polymorphisms of TLR4 Asp299Gly and TNF-α -308G/A in Leptospirosis - Nur Farhanah; Muhammad Hussein Gasem; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2016)
Background : TLR4 Asp299Gly and TNF-α -308G/A polymorphisms have been shown to be associated with increased susceptibility and severity of infection. TLR4 Asp299Gly polymorphism could affect the host’s ability to respond to leptospira sp. TNF-α -308G/A polymorphism, is associated with the high producer of TNF-α.Methods : Total of 36 leptospirosis patients (IgM anti leptospira and MAT positive) and healthy individual with the equal number were included. The polymorphisms were determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using site spesific restriction enzyme.Results : Distribution of homozygous wild-type TLR4 Asp299Gly polymorphism was higher in both of groups ( 94.5:97.2%.) and homozygous mutant allele was absent. There was not significantly difference of TLR4 Asp299Gly in leptospirosis patients and healthy group ( ρ=1.00; OR 0.5; 95%CI, 0.04-5.6) and between mild and severe leptospirosis (ρ=0.54; OR 1.54 ; 95% CI, 1.20-1.98). The presence of homozygous wild-type TNF-α -308G/A polymorphism was higher between leptospirosis patients and healthy group (100:94.5%) andhomozygous mutant allele was not found in both of the groups. No significantly different of TNF-α -308G>A polymorphism between leptospirosis patient and healthy group (ρ=0.49).Conclusions : In this study, the polymorphisms of TLR4 Asp299Gly and TNF-α -308G/A were not associated with the susceptibility and severity of leptospirosis.